Case report: Mesothelioma and BAP1 tumor predisposition syndrome: Implications for public health - Vimercati, Luigi; Cavone, Domenica; Fortarezza, Francesco; Delfino, Maria Celeste; Ficarella, Romina; Gentile, Angela; De Palma, Angela; Marulli, Giuseppe; De Maria, Luigi; Caporusso, Concetta; Marzullo, Andrea; d’Amati, Antonio; et al. (Frontiers in Oncology, 2022)
BRCA-1 associated protein 1 (BAP1) tumour predisposition syndrome (TPDS) is a hereditary condition characterised by germline mutation of the tumour suppressor BAP1. This disorder is associated with the development of various benign and malignant tumours, mainly involving the skin, eyes, kidneys, and mesothelium. In this article, we report the case of a man recruited through the Apulia (Southern Italy) Mesothelioma Regional Operational Centre of the National Register of Mesotheliomas, who suffered from uveal melanoma, renal cancer, and mesothelioma, and a familial cluster of BAP1 germline mutations demonstrat-ed by molecular analyses. The family members of the proband developed multiple malignancies. As tumours arising in this context have specific peculiarities in terms of clinical behaviour, identification of this condition through appropriate genetic counselling should be considered for adequate primary, secondary, and tertiary prevention measures for offspring.